Potential Commercial Applications of Nano-Surfactant in Enhanced Oil: Ni0.5Mn0.5Fe2O4-Chitosan Nanoparticles - Lian, Q.; Zheng, X.F. (Asian Journal of Chemistry, 2014)
Chitosan nanoparticles with magnetic properties can be potentially used as separation materials in adsorption of oil for enhanced oil recovery. Different from the traditional surfactants, the novel magnetic Ni0.5Mn0.5Fe2O4-chitosan nanoparticles has the advantage of excellent biodegradation and a high level of controllability. The Ni0.5Mn0.5Fe2O4-chitosan nanoparticles with core-shell structure was prepared successfully. The image of transmission electron microscope and the scanning electron microscopy showed that the cubic-shape magnetic Ni0.5Mn0.5Fe2O4 particles were encapsulated by the spherical chitosan nanoparticles. The size of the Ni0.5Mn0.5Fe2O4-chitosan nanoparticles were all below 100 nm. The saturated magnetization of the Ni0.5Mn0.5Fe2O4-chitosan nanoparticles could reach 80 emu/g and showed the characteristics of superparamagnetism at the same time. The evaluation on the interfacial properties of the product showed that the interfacial tension between crude oil and water could be reduce to ultra-low values as low as 10-3 mN/m when the magnetic Ni0.5Mn0.5Fe2O4-chitosan nanoparticle was used in several blocks in Shengli Oilfield without other additives. Meanwhile, the magnetic Ni0.5Mn0.5Fe2O4-chitosan nanoparticles possessed good salt-resisting capacity.